Effects of 6-week circuit training on anaerobic performance and simple reaction time in individuals with intellectual disability (ID) in Kelantan state - Nurul Azuar Hamzah,; Nur Syamsina Ahmad,; Farah Izzazaya Mohd Fariq,; Nur Shamimi Izzaty Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Participation in exercise benefits health and fitness among Intellectual Disability (ID) individuals. Circuit training is one of the exercise programme that can be tailored by manipulating the intensity, time and types of exercise. The purpose of the present study is to examine the effects of six weeks of circuit training on anaerobic fitness and simple reaction time in ID individuals. Thirty participants with mild to moderate ID were selected from individuals who are registered with the Pusat Pemulihan dalam Komuniti (PDK) and Yayasan Orang Kurang Upaya (YOKUK) in the Kelantan state. Participants were randomly divided into Circuit Training and Control groups. Participants in Circuit Training group followed a circuit training exercise programme, two times per week for six weeks, whereas participants in Control group were not involved in circuit training and carried out their regular activities. The anaerobic peak power anaerobic power of post-test was significantly improved (ƿ = 0.042) from the pre-test in Circuit Training group and it was also significantly higher (ƿ = 0.001) than Control group. There were no significant differences for the anaerobic capacity and simple reaction time between and within groups. Circuit training can be conducted to enhance anaerobic power in ID individuals, however longer participation may be needed to improve anaerobic capacity and simple reaction time.